John Grisham’s Megabestsellers - Christine Evain (Sillages Critiques)
110 million copies of John Grisham’s books have been published so far, and Grisham is now at the head of an elite of five “megabestselling” authors. Courted by Hollywood (ten screen adaptations so far), heavily promoted by the book industry and its distribution channels, Grisham’s international success makes him the number one world-wide bestselling author. Grisham cooked up his own recipe: a legal thriller which defies Todorov’s typology but which includes a certain number of the usual detective novel ingredients such as Eco’s Superman. The editor turns this market-driven product into one of its “megabestsellers” on which the book industry has now become commercially dependent.